Medication adherence/persistence among patients with active multiple sclerosis in Finland. (31st July 2020) - Lahdenperä, Sanni; Soilu‐Hänninen, Merja; Kuusisto, Hanna‐Maija; Atula, Sari; Junnila, Jouni; Berglund, Anders
Abstract : Objectives: To explore adherence, persistence, and treatment patterns in patients with multiple sclerosis (MS) in Finland treated with disease‐modifying therapies (DMTs) for active MS in 2005‐2018. Materials and Methods: The study cohort was identified using the Drug Prescription Register of Social Insurance Institute, Finland. All patients had at least one prescription of glatiramer acetate (GA), beta‐interferons, teriflunomide, or delayed‐release dimethyl fumarate (DMF). Adherence was calculated using proportion of days covered (PDC) (cutoff ≥0.8). Time to non‐persistence was calculated by the number of days on index DMT treatment before the first treatment gap (≥90 days) or switch and analyzed with time‐to‐event methodology. Results: The cohort included 7474 MS patients (72.2% female; mean age 38.9 years). Treatment switches were steady over 2005‐2012, peaked in 2015. PDC means (standard deviations) were GA, 0.87 (0.17); beta‐interferons, 0.88 (0.15); DMF, 0.89 (0.14); teriflunomide, 0.93 (0.10). Adherence frequencies were GA, 78.4%; beta‐interferons, 81.3%; DMF, 86.9%; teriflunomide, 91.7%. Logistic regression showed that age group, DMT and the starting year, sex, and hospital district independently affected adherence. Patients receiving teriflunomide and DMF, males, and older patients were more likely to persist on treatment. There was no difference in persistence between patients prescribed teriflunomide and DMF, or between GA and beta‐interferons. Conclusions: Oral DMTs had greater adherence and persistence than injectable DMTs.